The Effect of Educational Infrastructure, Family Support, and Learning Environment on Motivation and Learning Independence of SMA Negeri 1 Okbibab Students - Timotius T. M. Nalsa; Destri Sambara Sitorus; Bambang Ismanto (Journal of Educational Sciences, 2026)
This study aims to analyze the direct and indirect effects of educational infrastructure, family support, and the learning environment on the learning motivation and learning independence of students at SMA Negeri 1 Okbibab. Driven by the low levels of student independence in remote areas, this quantitative study surveyed 105 students selected via proportional stratified random sampling. Data gathered through structured questionnaires were evaluated using path analysis. The structural model analysis revealed an exceptionally high variance explanation, with an adjusted R-squared  value of 0.996 for learning independence. Statistical results confirmed that the learning environment (β = 0.455) and learning motivation (β = 0.964) have dominant positive effects on learning independence. Conversely, educational infrastructure showed unique negative path coefficients on both motivation (β = -0.343) and learning independence (β = -0.569). This statistical anomaly indicates that underutilized or severely limited physical facilities in 3T frontier areas can induce learning frustration, meaning that internal drives and immediate support systems like family carry far more weight in forming student autonomy. In conclusion, enhancing education in remote regions requires balancing external structural investments with targeted internal psychological strategies to cultivate sustainable student motivation and independent learning initiatives.